Антропонімічний вимір постмодерної літератури: монографія - Горенко Олена; Olena Gorenko; Horenko Olena (ЗУІ ім. Ф.Ракоці II-ТОВ «РІК-У», 2020)
Резюме. Монографія є продовженням дослідження «Антропонімічний вимір американського романтизму». Базуючись на теоретичних засадах, викладених у попередній розвідці, а також залучаючи інструментарій постмодерної критики (Р. Барт, Ж. Деррида, У. Еко, К. Леві-Строс, Ж. Лакан, Х. Блум, Ю.Крістева, П.Рікер) автор аналізує специфіку функціонування літературних антропонімів у творах сучасних знакових письменників. Розрахована на фахівців з історії та теорії літератури, викладачів та студентів вузів.

Abstract. This monography proposes a multifaceted methodological approach to the problem of literary name’s functioning in postmodern texts. Thus, in the article “The peculiarity of postmodern concept of the Proper name in the novels of M.Pavic, P.Constant, Haruki Murakami and P. Coelho” (“Специфіка постмодерної концепції імені у творах М.Павича, П.Констана, Х.Муракамі та П.Коельо”) the main accent is laid on mythological and esoteric aspects of literary names. Here the Proper name assumes quite a new status and performs a function of an active driving force. Attraction and repulsion between the names and their bearers make for dynamics of narrative discourse. All in all, historical, semiotic, mythocritical, hermeneutic and structural methods as well as phenomenological approach and devices of receptive aesthetics and linguistics are used in this monography to formulate a grounded analytical project which is inseparable from the general program of investigation – the concept of a Proper name.
https://kmf.uz.ua/wp-content/uploads/2020/11/olena-horenko-monograph_13-11-2020.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008468
Keywords: література постмодернізму; міфологічна та езотерична традиція